0098 Can simulation clarify diagnostic skills for newly qualified doctors?. (2nd November 2015) - Nagy, Annamaria; Scott-Smith, Wesley
Abstract : Background: Simulation based techniques are increasingly used in medical education as valuable tools complementing clinical experience and aiding the development of clinical skills in a risk-free environment. 1 Diagnostic reasoning is one of the essential skills that medical students need to develop by the time they take on their roles as junior doctors, and gain authority in decision making and case management. Diagnostic competence largely depends on repeated patient encounter leading to complex mental representations of diseases. 2 In light of restrictions applied to early clinical exposure during medical education due to ethical considerations on patient safety, simulation based techniques can be used to safely prepare students for effective medical practice. 3 This study will investigate the role of simulation for medical students facing the graduation transition as well as for junior doctors, focusing on their emerging competence in diagnostic reasoning. Methodology: Part 1: A systematic review is being conducted to summarise the literature on the role of SBME for final year medical students and newly qualified doctors, which are specifically geared towards diagnostic reasoning skills. Part 2: A mixed method qualitative study focusing on the graduation transition, using video consultations and simulated patients to examine changes in diagnostic skills. Anticipated results/outcomes: The use of simulation to assess and promote diagnostic reasoning skills of medical students facing the graduation transition has not yet received much research attention. The present study will enrich existing literature by improving our understanding of the diagnostic reasoning strategies used by students throughout the graduation transition. Potential impact: Building on previous findings, 4 this project will contribute to the mapping of the cognitive development of medical students as they acquire diagnostic competence throughout the continuum of medical education. It could help develop appropriate educational interventions to facilitate the graduation transition for medical students with regards to their diagnostic reasoning skills. References: McGaghie WC, Issenberg SB, Petrusa ER, Scalese RJ. A critical review of simulation‐based medical education research: 2003–2009. Med Educ. 2010;44:50–63 Eva KW. What every teacher needs to know about clinical reasoning. Med Educ. 2005;39:98–106 Bradley P. The history of simulation in medical education and possible future directions. Med Educ. 2006;40:254–262 Scott-Smith W. Diagnostic reasoning in medical students using a simulated environment, 2013, Doctoral thesis, University of Brighton